ASPEK EKONOMI PENDIDIKAN DALAM PENGEMBANGAN SUMBER DAYA MANUSIA - Ali Murdhani Ngandoh (AkMen JURNAL ILMIAH, 2012)
Education is a very important role in improving the quality of human resources. Education affects the full growth of a nation's economy. This is not only because education will affect the level of productivity, but also affect the fertility community. With education we can make human resources can be more responsive and ready to face any change in the workplace. Therefore, it is not surprising that the country has a population with a high level of education will have a rapid rate of economic growth